Agricultural growth linkages in Sub-Saharan Africa - Delgado, Christopher L.; Hopkins, Jane; Kelly , Valerie; Hazell, Peter B. R.; McKenna, Anna A.; Gruhn, Peter; Hojjati, Behjat; Sil, Jayashree; Courbois, Claude (International Food Policy Research Institute, 1998)
How much extra net income growth can be had in rural areas of Africa by increasing the spending power of local households? The answer depends on how rural households spend increments to income, whether the items desired can be imported to the local area in response to increased demand, and, if not, whether increased demand will lead to new local production or simply to price rises. For every dollar in new farm income earned, at least one additional dollar could be realized from growth multipliers, according to Agricultural Growth Linkages in Sub-Saharan Africa.